E-commerce operation empowers green agriculture: implication for the reduction of farmers' fertilizer usage - Hailan Qiu; Yi Huang; Weikun Zhang; Bing He; Ruolan Yuan; Zhipeng Wang (Frontiers in Sustainable Food Systems)
IntroductionHow e-commerce businesses improve farmers' fertilizer application (FFA) and reduced fertilizer application is of great practical significance.MethodsUsing the data from the China Rural Revitalization Survey (CRRS) in 2020, the OLS and mediating effect models were exploited to explore the impact and mechanism of e-commerce operation (EO) on FFA by examining this heterogeneous effect. We further explored the differences in fertilizer reduction effects of different EO's scales and modes.Results and discussionThe results show that e-commerce operation significantly negatively impacts farmers ' chemical fertilizer (CF), reducing CF's amount. The results of the mediating effect test show that agricultural machinery service plays an intermediary role in the influence of EO on FFA. The heterogeneity analysis shows that e-commerce operation has a heterogeneous impact on FFA regarding gender, agricultural functional zoning, and regional distribution. E-commerce operations can encourage women, major grain-producing areas, and farmers in the central and western regions to reduce fertilizer. Further discussion indicates that scale e-commerce and social e-commerce also perform the fertilizer reduction effect. Therefore, policy makers are suggested to encourage the transformation of rural industries into e-commerce to stimulate the production sector to reduce fertilizer use. These measures help developing countries balance economic growth and environmental protection, and promote sustainable ecological development.